Quick-curing high-stripping conductive adhesive film as well as preparation method and application thereof
By adopting a fast-solid high-release conductive adhesive film, the problem of high peeling force and rapid curing when the FPC film is bonded to the metal sheet is solved, and efficient conductive connection and shielding is achieved, with good stability and electrical performance.
Patent Information
- Application Number
- CN202510065622.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-29
AI Technical Summary
When the existing FPC film is bonded to metal sheets, it is difficult to meet the needs of high peeling force and rapid curing, which affects the stability and electrical performance of the bonding.
A fast-solid high-release conductive adhesive film is used, which consists of flexible acrylate/epoxy in situ polymer, polyphenoloxy resin, macromolecular epoxy resin, conductive powder, reactive diluent, coupling agent and surface treatment agent. Through specific formulation and processing technology, a conductive adhesive film with high peel toughness and rapid curing characteristics is formed.
It realizes efficient conductive connection and shielding between FPC and metal plate, has good peel strength, conductivity and fast curing properties, and can maintain good conductivity and bonding stability in high temperature and high humidity environments and after reflow soldering.
Smart Images

Figure CN119899599A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a fast-curing high-peeling conductive adhesive film and a preparation method and application thereof, belonging to the technical field of conductive adhesive materials and preparation thereof. Background Art
[0002] Flexible Printed Circuit (FPC) is a flexible printed circuit board with circuits formed on copper foil with flexible insulating film such as polyester PET film or polyimide PI film as the substrate. FPC has the characteristics of high wiring density, free bending and folding, three-dimensional assembly, thin thickness and light weight. By embedding circuit design on FPC, a large number of precision components can be stacked in a narrow and limited space to form a flexible and bendable circuit. As electronic products develop towards light, thin, short and small, FPC has been increasingly widely used in integrated circuits of aerospace electronics, new energy vehicle electronic control and medical equipment. In order to ensure the normal operation of electronic equipment and personal safety during use, and to enhance the reliability and electrical performance of electronic products, the ground wire of FPC needs to be connected to the housing of the electronic equipment to prevent leakage from damaging other parts and affecting the use of the equipment, as well as interference to the equipment caused by static electricity. Grounding on FPC usually refers to electrically connecting the negative pole of the power supply on the FPC (except for positive and negative dual power supply) to the metal casing, so that the metal casing is at zero potential. After the FPC is grounded, the metal casing can shield the interference waves radiated outward by the equipment and shield external interference.
[0003] The electrical connection and shielding effect of FPC or metal plate and conductive metal sheet can be achieved by conductive glue or conductive paste. However, when conductive glue or conductive paste is used for FPC bonding, on the one hand, there is a problem of glue overflow at the bonding edge and the thickness of the glue layer is difficult to accurately control. On the other hand, the liquid conductive glue dispensing technology has construction efficiency problems for bonding over a large area. Therefore, film-like conductive glue has outstanding technical advantages in FPC conductive connection. Since the viscosity of the conductive adhesive film is high during the curing process, the glue overflow during the pressurization process is precisely controllable, and the glue layer is more uniform and precise. At the same time, the film-like conductive adhesive can be pre-die-cut or laser-cut to achieve full automation of the application, lamination, and curing processes, greatly improving production efficiency.
[0004] Traditional FPC is mainly used for electrical connection, and its organic film mostly uses polyester film (PET film) and polyimide film (PI film). With the rapid development of high-performance integrated circuits, FPC is becoming more and more integrated, high-density and high-functional, so the requirements for the heat resistance of FPC film (such as resistance to solder bath, etc.) are also getting higher and higher. At present, more and more FPC films use thermoplastic polyimide PI materials. The PI film in FPC needs to be bonded to the metal sheet or casing of the electronic equipment, and a conductive connection is formed with the metal sheet through the punched part on the FPC board to ensure the stability, reliability, safety and electrical performance of the electronic equipment during use, and prevent damage and interference to the equipment caused by leakage and static electricity. When the PI film of FPC is bonded to metal sheets such as stainless steel, copper or aluminum sheets, it must have good peeling force, and the curing process must be fast and efficient. Therefore, it is very necessary to provide a fast-curing high-peeling conductive adhesive film for electrical connection or shielding conductive bonding between FPC and metal plates. Summary of the invention
[0005] The present invention provides a fast-curing high-peeling conductive adhesive film and a preparation method and application thereof to achieve conductive connection between a PI-based FPC and a metal shell of an equipment.
[0006] The technical solution of the present invention:
[0007] One of the purposes of the present invention is to provide a fast-curing high-peeling conductive adhesive film, which comprises a base film and a conductive adhesive layer coated on the base film;
[0008] The conductive adhesive is made of the following raw materials in parts by mass: 80-100 parts of flexible acrylate / epoxy in-situ polymer, 5-15 parts of liquid bisphenol epoxy resin, 40-55 parts of polyphenol oxide resin and / or macromolecular epoxy resin, 270-330 parts of conductive powder, 10-20 parts of active diluent, 3-6 parts of coupling agent and surface treatment agent, and 3-6 parts of dicyandiamide and imidazole derivative curing accelerator or liquid modified dicyandiamide curing agent.
[0009] Further defined, the base film is a PET film with a thickness of 50-100 μm
[0010] It is further defined that the liquid bisphenol epoxy is bisphenol A epoxy resin, bisphenol F epoxy resin or bisphenol F epoxy oligomer.
[0011] Further defined, the weight average molecular weight Mw of the polyphenol oxide resin is 5×10 4 ~7×10 4 , the glass transition temperature is 83-86°C; the epoxy equivalent of the macromolecular epoxy resin is 600-900g / eq.
[0012] It is further defined that the reactive diluent is a polyether epoxy and / or a polyether amine.
[0013] It is further defined that the conductive powder is one or more of flaky micron silver powder, dendritic silver-plated copper powder, and flaky silver-plated copper powder.
[0014] It is further defined that the conductive powder is dendritic silver-plated copper powder.
[0015] It is further defined that the coupling agent is KH-560 and the surface treatment agent is ascorbic acid.
[0016] It is further defined that the conductive film has a thickness of 40 to 100 μm, an initial peel strength of ≥ 22 N / cm, and a volume resistivity of ≤ 5×10 -3 Ω·cm.
[0017] It is further defined that a defoaming agent is added to the conductive adhesive.
[0018] It is further defined that the defoaming agent is BYK-A530.
[0019] It is further defined that the solvent used for preparing the conductive adhesive film is ethyl acetate, and the mass ratio of the solvent to the total mass ratio of the raw materials for preparing the conductive adhesive layer is 1:(0.8-1.3).
[0020] The second object of the present invention is to provide a method for preparing the above-mentioned conductive adhesive film, which specifically comprises the following steps:
[0021] (1) dissolving the flexible acrylate / epoxy in-situ polymer and the liquid bisphenol epoxy resin in ethyl acetate, stirring and mixing them uniformly at 50 to 60° C., and cooling to room temperature to obtain a premixed resin A;
[0022] (2) dissolving the polyphenol oxide resin and / or the macromolecular epoxy resin in ethyl acetate, stirring and mixing at 50 to 60° C., and cooling to room temperature to obtain a premixed resin B;
[0023] (3) mixing the conductive powder, the active diluent, the coupling agent and the surface treatment agent, and uniformly dispersing them by a high-speed disperser to obtain a premixed powder C;
[0024] (4) After mixing the premixed resin A, the premixed resin B and the premixed powder C, dicyandiamide and an imidazole derivative curing accelerator or a liquid modified dicyandiamide curing agent are added and mixed evenly to obtain a conductive paste;
[0025] (5) coating the conductive paste on the base film, drying it, and rolling it up to obtain a conductive adhesive film.
[0026] It is further defined that the preparation method of the flexible acrylate / epoxy in-situ polymer in (1) is: long-chain acrylate and DER354 epoxy resin are mixed in a mass ratio of 8:2, benzoyl peroxide is used as an initiator, and the mixture is reacted at 70 to 80° C. for 4 to 6 hours to obtain a flexible acrylate / epoxy in-situ polymer.
[0027] It is further defined that (3) the rotation speed of the medium- and high-speed disperser is 1000 to 2000 rpm.
[0028] It is further defined that ethyl acetate solvent is added in (4) so that the mass ratio of the solvent to the total mass ratio of the raw materials for preparing the conductive adhesive layer is 1:(0.8-1.3).
[0029] It is further defined that in (5), a drying tunnel is used for drying, the length of the drying tunnel is 6 m, the set temperatures are 40° C., 80° C., 90° C., 110° C., 80° C. and 40° C. in sequence, and the passing speed is 0.3-1.0 m / min.
[0030] The second object of the present invention is to provide a method for using the above conductive adhesive film, specifically: pressing for 2 to 3 minutes at 160 to 170°C and 2 to 3 MPa; and then heating and curing at 150°C for 60 minutes.
[0031] The third object of the present invention is to provide an application of the above-mentioned conductive adhesive film, specifically for electrical connection or shielding conductive bonding between FPC and metal plate.
[0032] Beneficial effects:
[0033] (1) The present invention uses a flexible acrylate / epoxy in-situ polymer with a weight average molecular weight Mw of 5×10 4 ~7×10 4 The main components are polyphenol oxide resin and macromolecular epoxy with epoxy equivalent weight of more than 600g / eq. Macromolecular epoxy and elastomer are used to provide film-forming properties, control rheological properties and high peel toughness, and the conductivity is improved by adding metal powder. As well as resin latent curing technology, epoxy resin, curing agent and accelerator are used together to achieve rapid curing and molding of the film under the conditions of 2-3MPa and 160-170℃ in 2-3min, forming a thermosetting cross-linking network, improving adhesion and heat resistance, and preparing a rapidly curable isotropic conductive film.
[0034] (2) The conductive adhesive film prepared by the present invention has a thickness of 40 to 100 μm and has good flexibility, film-forming property, conductivity, adhesion and fast curing properties. Among them, the flexibility and film-forming property enable it to be die-cut and formed, with neat edges and precise dimensions, the conductivity enables it to meet the functional requirements of conductive grounding and shielding, the adhesion enables the PI film of the FPC to form good mechanical strength to ensure stable and reliable connection, and the fast curing property is conducive to automated mass production, improving the utilization efficiency of fast pressing equipment and the production efficiency of automated processes.
[0035] (3) The present invention first dissolves and mixes the acrylate / epoxy in-situ polymer and the thermoplastic resin in a solvent, thereby providing a rheological basis for subsequent film-forming properties and fast-setting adhesion properties; then, the conductive powder is mixed with a surface treatment agent, a coupling agent, and an active diluent and dispersed by high-speed shearing to improve the wettability of the surface treatment agent on the powder surface; finally, a curing agent is added, and the conductive adhesive slurry is coated on the base film by a casting method, and further passes through a drying oven at 80-110°C, where the solvent evaporates in the drying oven and is discharged through an air duct. The conductive slurry is semi-cured under heating conditions, so that the conductive slurry film has a matte metallic luster and a non-sticky surface, and is directly rolled up to obtain a fast-setting conductive adhesive film.
[0036] (3) In order to achieve the conductivity of the film in the present invention, conductive powder is added, and the conductivity of the film is controlled by adjusting the amount of conductive powder (volume resistivity ≤ 5×10 -3 Ω·cm). Surface treatment agents and interface additives are used to adjust and improve the wettability of resin and conductive powder, reduce bubble defects, improve the surface state of the film and the dispersibility of the conductive powder.
[0037] (4) The test shows that the isotropic conductive adhesive film prepared by the present invention is a pre-cured film-like conductive adhesive material with high peel toughness and can be quickly cured and formed. When used for bonding PI and stainless steel, the 90° peel strength is ≥22N / cm and the volume resistivity is ≤5×10 -3 Ω·cm, can be quickly cured and bonded in 2-3min at 2-3MPa and 160-170℃. When used for FPC bonding, the grounding resistance of 1.0mm GND hole is ≤0.05Ω, and the bonding strength retention rate is above 80% after reflow soldering at 85℃ / 85%RH / 500h and 260℃ / 5s. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a schematic diagram of the bonding structure of the FPC board and the stainless steel sheet through the conductive adhesive film. DETAILED DESCRIPTION
[0039] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0040] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0041] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0042] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0043] Implementation
[0044] The fast-curing high-peeling conductive adhesive film provided in this embodiment includes a base film and a conductive adhesive layer coated on the base film;
[0045] The conductive adhesive is made of the following raw materials in parts by weight: 80-100 parts of flexible acrylate / epoxy in-situ polymer, 5-15 parts of liquid bisphenol epoxy resin, 40-55 parts of polyphenol oxide resin and / or macromolecular epoxy resin, 270-330 parts of conductive powder, 10-20 parts of active diluent, 3-6 parts of coupling agent and surface treatment agent, and 3-6 parts of dicyandiamide and imidazole derivative curing accelerator or liquid modified dicyandiamide curing agent.
[0046] The formula composition and processing technology of conductive adhesive have a great influence on the performance of conductive adhesive film. The conductive powder in the conductive adhesive formula mainly plays the role of electrical conduction and thermal conduction. One or more of dendritic powder (silver powder or silver-plated copper powder) and flaky powder (silver powder or silver-plated copper powder) are used in combination. Micron-level high-conductivity conductive powder is selected, and the addition ratio is optimized (50-70% wt of the total mass of the film) to achieve higher conductivity efficiency. The adhesive material part is mainly composed of epoxy resin, thermoplastic resin, elastomer, active diluent, curing agent, accelerator, surface treatment agent and interface additive. Thermoplastic resin and elastomer provide film-forming properties, control rheological properties and high peel toughness. The thermoplastic resin uses polyphenol oxide resin or macromolecular epoxy, and the weight average molecular weight Mw of polyphenol oxide resin is 5×10 4 ~7×10 4, the glass transition temperature is 83-86℃, and it is soluble in solvents such as acetone, butanone, and ethyl acetate. The macromolecular epoxy is an epoxy resin with an epoxy equivalent of 600-900g / eq. Although there is an epoxy group at the end of the molecule, it can participate in the cross-linking reaction during the curing process, but because the epoxy content is low, it is more thermoplastic, so it is classified as a thermoplastic resin with active end groups. Acrylate in-situ polymer and thermoplastic resin are used as the main resin of conductive film adhesive materials. Among them, acrylate in-situ polymer can greatly improve the peeling toughness of epoxy and give the adhesive film-forming properties after semi-curing. Acrylate in-situ polymer has good miscibility stability with epoxy resin and can form a cross-linking network together with the curing agent.
[0047] The acrylate in-situ polymer is a long-chain acrylate, such as isooctyl acrylate and butyl acrylate, and an acrylate epoxy free radical polymer, wherein the long-chain acrylate accounts for 80% of the total reactant. The free radical polymerization reaction is carried out in a bisphenol F epoxy resin DER354 medium, with benzoyl peroxide as an initiator, and reacted at 70-80°C for 4-6 hours to prepare an acrylate epoxy in-situ polymer containing an epoxy functional group, namely, an acrylate / epoxy in-situ polymer.
[0048] The curing agent is dicyandiamide curing agent or modified liquid dicyandiamide. Dicyandiamide is a commonly used curing agent for epoxy resin, which has the characteristics of good latency and fast curing. However, the curing temperature of dicyandiamide is relatively high, and usually it takes more than 170°C to cure epoxy. Therefore, imidazole derivative curing accelerators are used to promote dicyandiamide to cure epoxy or liquid modified dicyandiamide is used to cure epoxy.
[0049] The coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane containing epoxy group, namely KH-560 silane coupling agent.
[0050] Ascorbic acid is selected as the surface treatment agent. A small amount of ascorbic acid has antioxidant ability on the metal surface and can improve the conductivity of the conductive film during processing and preparation.
[0051] Epoxy resin, curing agent and accelerator are used together to achieve rapid curing and molding at 2-3MPa and 160-170℃ for 2-3min, forming a thermosetting cross-linking network to improve adhesion and heat resistance; active diluent is used to reduce resin viscosity and provide good coating and surface smoothness.
[0052] Surface treatment agents and interface additives are used to adjust and improve the wettability of resin and conductive powder, reduce bubble defects, and improve the surface condition of the film.
[0053] The specific method for preparing the acrylate / epoxy in-situ polymer used in the following examples is as follows: 80 g of isooctyl acrylate and 20 g of DER354 epoxy resin are mixed, 0.5 g of benzoyl peroxide is added as an initiator, and the mixture is reacted at 70° C. for 5 h to obtain a flexible acrylate / epoxy in-situ polymer.
[0054] The liquid bisphenol epoxy is bisphenol F type epoxy resin DER354.
[0055] The polyphenol oxide resin has a weight average molecular weight Mw of 5×10 4 ~7×10 4 Holy Spring SQP40.
[0056] The macromolecular epoxy resin is Nan Ya 904 epoxy.
[0057] The active diluent is EPG207 and / or polyetheramine D230.
[0058] The coupling agent is KH560.
[0059] The curing agent liquid dicyandiamide is Ajinomoto F111; the superfine dicyandiamide is Azken 100SF; and the imidazole derivative accelerator is ARADUR9506.
[0060] The defoamer is BYK-A530.
[0061] Example 1
[0062] Step 1: Mix 10 parts by weight of bisphenol F epoxy DER354, 90 parts by weight of acrylate / epoxy in-situ polymer and 30 parts by weight of ethyl acetate solvent, heat to 55° C. in a container, stir and mix evenly, and cool to room temperature to prepare premixed resin A.
[0063] Step 2: Dissolve 50 parts of Shengquan SQP40 polyphenol oxide resin in 180 parts of ethyl acetate solvent, heat to 55° C. in a container, stir and mix evenly, and cool to room temperature to prepare premixed resin B.
[0064] Step 3: Place 10 parts of active diluent EPG207, 10 parts of polyetheramine D230, 2 parts of silane coupling agent KH560, 4 parts of ascorbic acid, 0.3 parts of defoaming agent, 270 parts of 2-10 μm flaky silver powder and 60 parts of ethyl acetate solvent in a high-speed disperser, and disperse them evenly at a speed of 1500 rpm to prepare a premixed powder C.
[0065] Step 4: Evenly mix 5 parts of F111 liquid dicyandiamide curing agent with premixed resin A, premixed resin B and premixed powder C to prepare a conductive paste for coating.
[0066] Step 5: Pour the conductive slurry for coating into a stirring container, and use a peristaltic pump to control the flow rate to continuously introduce the conductive slurry into the middle of the comma coating roller 5-10 cm away from the baffle.
[0067] Step 6: Coat the conductive adhesive paste on the PET film (10 μm) by the casting method, and put it into a 6m long drying tunnel for drying, wherein the setting temperature of the drying tunnel is 40°C, 80°C, 90°C, 110°C, 80°C and 40°C. The conductive paste forms a uniform film on the PET, the solvent evaporates in the drying tunnel and is discharged through the air duct, and the conductive paste is semi-cured under heating conditions, and the semi-curing degree of the conductive paste is controlled by adjusting the casting speed, and the specific casting speed is 1.6m / min.
[0068] Step 7: The semi-cured conductive film coming out of the drying oven has a matte metallic luster and a non-sticky surface. A tension of 40N is applied to directly roll up the PET film coated with the conductive film to obtain the conductive film.
[0069] Example 2
[0070] The difference between this embodiment and embodiment 1 is that: in step 1, the amount of bisphenol F epoxy DER354 used is 15 parts; in step 3, the amount of active diluent EPG207 used is 5 parts, ascorbic acid is 3 parts, and 2-10 μm flaky silver powder is 300 parts; the remaining process steps and parameter settings are the same as those in embodiment 1.
[0071] Example 3
[0072] The difference between this embodiment and embodiment 1 is that: in step 1, the amount of bisphenol F epoxy DER354 used is 15 parts; in step 2, 45 parts of Shengquan SQP40 polyphenol oxide resin are used; in step 3, 3 parts of ascorbic acid are used, 300 parts of 2-10 μm dendritic silver-plated copper powder (8% silver-plated) and 30 parts of silver-plated flaky copper powder (5% silver-plated) are used to replace 270 parts of 2-10 μm flaky silver powder in embodiment 1; in step 4, 4 parts of ultrafine dicyandiamide and 1 part of imidazole derivative accelerator are used to replace 5 parts of F111 liquid dicyandiamide curing agent in embodiment 1; the remaining process steps and parameter settings are the same as those in embodiment 1.
[0073] Example 4
[0074] The difference between this embodiment and embodiment 1 is that: in step 2, 40 parts of Shengquan SQP40 polyphenol oxide resin and 10 parts of macromolecular solid epoxy (Nan Ya 904 epoxy) are used to replace 50 parts of Shengquan SQP40 polyphenol oxide resin in embodiment 1; in step 3, 3 parts of ascorbic acid, 270 parts of 2-10μm dendritic silver-plated copper powder (8% silver-plated) and 30 parts of silver-plated flake copper powder (5% silver-plated) are used to replace 270 parts of 2-10μm flake silver powder in embodiment 1; in step 4, 4 parts of ultrafine dicyandiamide and 1 part of imidazole derivative accelerator are used to replace 5 parts of F111 liquid dicyandiamide curing agent in embodiment 1; the remaining process steps and parameter settings are the same as those in embodiment 1.
[0075] Example 5
[0076] The difference between this embodiment and embodiment 1 is that: in step 2, 40 parts of Shengquan SQP40 polyphenol oxide resin and 10 parts of macromolecular solid epoxy (Nan Ya 904 epoxy) are used to replace 50 parts of Shengquan SQP40 polyphenol oxide resin in embodiment 1; in step 3, 3 parts of ascorbic acid and 270 parts of 2-10μm dendritic silver-plated copper powder (8% silver-plated) are used to replace 270 parts of 2-10μm flaky silver powder in embodiment 1; the remaining process steps and parameter settings are the same as those in embodiment 1.
[0077] Example 6
[0078] The difference between this embodiment and embodiment 1 is that: in step 1, the amount of bisphenol F epoxy DER354 used is 15 parts, and the acrylate / epoxy in-situ polymer is 95 parts; in step 2, 40 parts of Shengquan SQP40 polyphenol oxide resin and 10 parts of macromolecular solid epoxy (Nan Ya 904 epoxy) are used to replace 50 parts of Shengquan SQP40 polyphenol oxide resin in embodiment 1; in step 3, the amount of active diluent EPG207 used is 5 parts, polyetheramine D2305 parts, and ascorbic acid 3 parts, and 270 parts of 2-10μm dendritic silver-plated copper powder (8% silver-plated) are used to replace 270 parts of 2-10μm flaky silver powder in embodiment 1; the remaining process steps and parameter settings are the same as those in embodiment 1.
[0079] Comparative Example 1
[0080] The difference between this comparative example and Example 1 is that in step 3, 0 parts of ascorbic acid are used, and the remaining process steps and parameter settings are the same as those in Example 1.
[0081] Comparative Example 2
[0082] The difference between this comparative example and Example 2 is that in step 3, there is 0 part of ascorbic acid, and the remaining process steps and parameter settings are the same as those in Example 2.
[0083] Comparative Example 3
[0084] The difference between this comparative example and Example 3 is that in step 3, there is 0 part of ascorbic acid, and the remaining process steps and parameter settings are the same as those in Example 3.
[0085] Comparative Example 4
[0086] The difference between this comparative example and Example 4 is that in step 3, 1 part of ascorbic acid, 260 parts of dendritic silver-plated copper powder (8% silver-plated), and 50 parts of silver-plated flake copper powder (5% silver-plated) are used; the remaining process steps and parameter settings are the same as those in Example 4.
[0087] Comparative Example 5
[0088] The difference between this comparative example and Example 5 is that: in step 1, 100 parts of acrylate / epoxy in-situ polymer are used; in step 3, 1 part of ascorbic acid, 240 parts of dendritic silver-plated copper powder (8% silver-plated), and 60 parts of silver-plated flake copper powder (5% silver-plated) are used; the remaining process steps and parameter settings are the same as those in Example 4.
[0089] The curing and post-curing test conditions of the conductive adhesive films prepared in the above Examples 1 to 6 and Comparative Examples 1 to 5 are as follows:
[0090] (1) Fast pressing conditions: 170℃ / 3MPa / 3min.
[0091] (2) Curing conditions: 150°C / 60min.
[0092] (3) 90° peel strength: The bonded materials are PI film / stainless steel, the PI film has a width of 10 mm and a thickness of 25 μm, the Ni-304 stainless steel sheet has a thickness of 200 μm, and the peeling speed is 50 mm / min.
[0093] (4) Grounding resistance: The diameter of the line grounding terminal GND is 1.0 mm. The resistance of the PI-based FPC board / Ni-304 stainless steel sheet after quick pressing and heat curing is measured using a micro-ohmmeter. Figure 1 shown.
[0094] (5) Volume resistivity: in accordance with QJ 1523-1988 standard.
[0095] The test results are shown in Table 1 and Table 2:
[0096] Table 1 Example 1 to Example 6
[0097]
[0098] Reflow: 260℃5s, 3 times
[0099] Table 2 Comparative Examples 1 to 5
[0100]
[0101]
[0102] Reflow: 260℃5s, 3 times
[0103] As shown in Table 1, the peel strength PI / stainless steel 90° peel strength of the conductive film prepared by silver powder and silver-plated copper powder is ≥22N / cm, and the volume resistivity is ≤5×10 -3 Ω·cm, can be quickly cured and bonded in 2-3min under 2-3MPa and 160-170℃, used for FPC bonding The grounding resistance of the ground connection GND is ≤50mΩ, and the conductivity and bonding strength retention rate are above 80% after reflow soldering at 85℃ / 85%RH / 500h and 260℃ / 5s.
[0104] In Example 1 and Example 2, the conductive powder is pure silver powder, and the volume resistivity after curing is low, both within 1×10 -3 ~2×10 -3 Ωcm, but the cost of silver is relatively high. Considering the cost of industrial batch production, silver-plated copper powder is preferred. In Examples 3 and 4, silver-plated copper powder is used. When the addition amount is 65% by weight, the resistivity is low. When the addition amount is 60%, the volume resistivity is between 3×10 -3 ~4×10 -3 The grounding resistance in Examples 1-6 also showed a similar trend, which may be due to the better oxidation resistance of silver, but the difference with the silver-plated copper powder was not significant.
[0105] From Table 1 and Table 2 above, it can be seen from the comparison between Examples 1 to 5 and Comparative Examples 1 to 5 that ascorbic acid is not added, and the amount of latent curing agent and thermoplastic resin, in-situ polymerized acrylate and epoxy corresponds to that of the embodiment. The test results of conductivity, adhesion and processability of Comparative Examples 1-5 are shown in Table 2. As can be seen from Table 2, the initial PI / stainless steel 90° peel strength of the conductive adhesive film prepared using silver powder and silver-plated copper powder is ≥20N / cm, and the volume resistivity is ≤5×10 -3 Ωcm, can be quickly cured and bonded in 2-3min under 2-3MPa and 160-170℃, used for FPC bonding The grounding resistance of the aperture is ≤50mΩ. However, the resistance increases after reflow soldering at 85℃ / 85%RH / 500h and 260℃ / 5s. In Comparative Examples 1 and 2, the conductive powder is pure silver powder, which has better oxidation resistance than silver-plated copper powder. The volume resistivity is low after curing. After 85℃ / 85%RH / 500h, the grounding resistance is still below 50mΩ, and the bonding strength can still be maintained above 15N / cm. However, in Comparative Examples 3 to 5, silver-plated copper powder (silver content 8%) is used as the conductive powder, and its oxidation resistance is lower than that of silver powder. After 85°C / 85%RH / 500h, the peel strength is around 13N / cm, and Comparative Example 5 is even lower than 13N / cm. After 85°C / 85%RH / 500h, the grounding resistance is above 50mΩ, and the grounding resistance after 3 reflows is still below 50mΩ. The reason may be that although the reflow temperature is high (260°C), the time is short, and the resistance change of the conductive film is not as significant as the result of the double 85 test. At the same time, in Comparative Example 5, since the amount of acrylic acid in-situ polymer is increased by 10 parts, the viscoelasticity of the film becomes higher, and the neatness of the die-cutting edge is slightly worse.
[0106] In summary, the conductive adhesive film prepared in the present application has excellent peel strength, good conductivity and high-temperature fast-solidification pressing performance, and still maintains good conductivity and bonding stability in high temperature and high humidity environment and after reflow soldering, and can be used for conductive and shielding bonding of integrated circuit boards such as FPC boards and metal sheets.
[0107] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A fast-curing high-peeling conductive adhesive film, characterized in that: It includes a base film and a conductive adhesive layer coated on the base film; The conductive adhesive is made of the following raw materials in parts by mass: 80-100 parts of flexible acrylate / epoxy in-situ polymer, 5-15 parts of liquid bisphenol epoxy resin, 40-55 parts of polyphenol oxide resin and / or macromolecular epoxy resin, 270-330 parts of conductive powder, 10-20 parts of active diluent, 3-6 parts of coupling agent and surface treatment agent, and 3-6 parts of dicyandiamide and imidazole derivative curing accelerator or liquid modified dicyandiamide curing agent.
2. The conductive adhesive film according to claim 1, characterized in that: The liquid bisphenol epoxy is bisphenol A epoxy resin, bisphenol F epoxy resin or bisphenol F epoxy oligomer.
3. The conductive adhesive film according to claim 1, characterized in that: The weight average molecular weight Mw of polyphenol oxide resin is 5×10 4 ~7×10 4 ; The epoxy equivalent of macromolecular epoxy resin is 600~900g / eq.
4. The conductive adhesive film according to claim 1, characterized in that: Reactive diluents polyether epoxy and / or polyether amine.
5. The conductive adhesive film according to claim 1, characterized in that: The conductive powder is one or more of flaky micron silver powder, dendritic silver-plated copper powder and flaky silver-plated copper powder; the coupling agent is KH-560, and the surface treatment agent is ascorbic acid.
6. The conductive adhesive film according to claim 1, characterized in that: Defoaming agent is added to the conductive adhesive.
7. The conductive adhesive film according to claim 1, characterized in that: The thickness of the conductive film is 40-100 μm, the initial peel strength is ≥22 N / cm, and the volume resistivity is ≤5×10 -3 Ω·cm.
8. A method for preparing a conductive adhesive film according to any one of claims 1 to 7, characterized in that: include: (1) dissolving the flexible acrylate / epoxy in-situ polymer and the liquid bisphenol epoxy resin in ethyl acetate, stirring and mixing them uniformly at 50 to 60° C., and cooling to room temperature to obtain a premixed resin A; (2) dissolving the polyphenol oxide resin and / or the macromolecular epoxy resin in ethyl acetate, stirring and mixing at 50 to 60° C., and cooling to room temperature to obtain a premixed resin B; (3) mixing the conductive powder, the active diluent, the coupling agent and the surface treatment agent, and uniformly dispersing them by a high-speed disperser to obtain a premixed powder C; (4) After mixing the premixed resin A, the premixed resin B and the premixed powder C, dicyandiamide and an imidazole derivative curing accelerator or a liquid modified dicyandiamide curing agent are added and mixed evenly to obtain a conductive paste; (5) coating the conductive paste on the base film, drying it, and rolling it up to obtain a conductive adhesive film.
9. A method for using the conductive adhesive film according to any one of claims 1 to 7, characterized in that: The method of use is: press for 2 to 3 minutes at 160 to 170° C. and 2 to 3 MPa; then heat and cure at 150° C. for 60 minutes.
10. Use of the conductive adhesive film according to any one of claims 1 to 7, characterized in that: Used for electrical connection or shielding conductive bonding between FPC and metal plate.